TOTAL QUALITY CONTROL IN CAREGIVER PRACTICE: IMPROVING THE QUALITY OF CENTER CONSTRUCTION AND DEVELOPMENT HOLISTICALLY - Setiawan, Muhammad Bakron Andre; Amin, Muhammad Fathul; Manshur, Umar; Jazilurrahman, Jazilurrahman; Rifa'i, Moh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
construction and development of centri through Total Quality Control in the Practice of Fallout. The researchers use a qualitative method aimed at explaining the truth of a phenomenon that has the aim of obtaining objective data. Based on the results of the research, it can be concluded that there are three stages that are carried out by Pondok Pesantren Nurul Jadid in carrying out quality development. First, to follow the Furudul Ainiyah Construction Program (FA 3 months). Second, to take the FA Graduation Test. Third, to move to the development hostel according to the talent and interests of the centre. In addition, it also shows that the application of Total Quality Control (TQC) in the practice of Walisuh as a method of construction and development of the center has brought a significant positive impact. Thus, the integration of TQC into Walisuh practices can be seen as a strategic step to improve the quality of construction and development of the centre holistically.